Polymorphisms of a Collagen-Like Adhesin Contributes to Legionella pneumophila Adhesion, Biofilm Formation Capacity and Clinical Prevalence - Abdel-Nour, Mena; Su, Han; Duncan, Carla; Li, Shaopei; Raju, Deepa; Shamoun, Feras; Valton, Marine; Ginevra, Christophe; Jarraud, Sophie; Guyard, Cyril; Kerman, Kagan; Terebiznik, Mauricio R. (Frontiers in Microbiology, 2019)
Legionellosis is a severe respiratory illness caused by the inhalation of aerosolized water droplets contaminated with the opportunistic pathogen Legionella pneumophila. The ability of L. pneumophila to produce biofilms has been associated with its capacity to colonize and persist in human-made water reservoirs and distribution systems, which are the source of legionellosis outbreaks. Nevertheless, the factors that mediate L. pneumophila biofilm formation are largely unknown. In previous studies we reported that the adhesin Legionella collagen-like protein (Lcl), is required for auto-aggregation, attachment to multiple surfaces and the formation of biofilms. Lcl structure contains three distinguishable regions: An N-terminal region with a predicted signal sequence, a central region containing tandem collagen-like repeats (R-domain) and a C-terminal region (C-domain) with no significant homology to other known proteins. Lcl R-domain encodes tandem repeats of the collagenous tripeptide Gly-Xaa-Yaa (GXY), a motif that is key for the molecular organization of mammalian collagen and mediates the binding of collagenous proteins to different cellular and environmental ligands. Interestingly, Lcl is polymorphic in the number of GXY tandem repeats. In this study, we combined diverse biochemical, genetic, and cellular approaches to determine the role of Lcl domains and GXY repeats polymorphisms on the structural and functional properties of Lcl, as well as on bacterial attachment, aggregation and biofilm formation. Our results indicate that the R-domain is key for assembling Lcl collagenous triple-helices and has a more preponderate role over the C-domain in Lcl adhesin binding properties. We show that Lcl molecules oligomerize to form large supramolecular complexes to which both, R and C-domains are required. Furthermore, we found that the number of GXY tandem repeats encoded in Lcl R-domain correlates positively with the binding capabilities of Lcl and with the attachment and biofilm production capacity of L. pneumophila strains. Accordingly, the number of GXY tandem repeats in Lcl influences the clinical prevalence of L. pneumophila strains. Therefore, the number of Lcl tandem repeats could be considered as a potential predictor for virulence in L. pneumophila isolates.